Praktek Penggunaan Virtual Account untuk Menunjang Keberhasilan Operasional Kelembagaan di Yogyakarta - Aurelia Melinda Nisita Wardhani; Ima Kristina Yulita (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
So far, the administrative records of Foundation X's receipts have not gone well. This causes financial reporting to be less transparent and accountable. The purpose of this training is to introduce the payment system mechanism through a virtual account to employees in work units in this organization so that it can help administration become better, especially transparency in revenue sources that will be used to support operational activities. The method used in this training is lectures, followed by group discussion forums and virtual account practice/simulation. As a result of the training activities, participants have knowledge about the advantages and disadvantages of the payment system and are more confident and more prepared to use virtual accounts to serve parties who will carry out transactional activities with this this foundation.